Growth rate estimation by 210Pb chronology in precious corals collected off the southern coast of Japan - Yamada, Masatoshi; Suzuki, Atsushi; Iwasaki, Nozomu (Frontiers in Marine Science, 2023)
The Lead 210 (210Pb) concentrations were determined to estimate the skeletal growth rates in the four species of precious corals including Japanese red coral (Corallium japonicum), pink coral (Pleurocorallium elatius), white coral (P. konojoi), and a deep-sea coral (Coralliidae sp.), and in a bamboo coral (Keratoisis sp.). Colonies were collected from the southern coast of Japan, western North Pacific margin. The 210Pb concentrations typically showed the exponential decrease with distance from the edge to the center of the skeleton axis in a cross section of main stem of colonies. The mean radial growth rates for colonies were estimated from the slopes of the best fit curves for exponential decrease in 210Pb concentration along the multiple transects. The obtained mean and standard deviation of radial growth rates in the diameter (the number of transects, n) for three colonies of C. japonicum were 0.31 mm/y (n = 1), 0.21 ± 0.05 mm/y (n = 2), and 0.36 ± 0.13 mm/y (n = 2), respectively, which were broadly comparable to the previously reported growth rates obtained by growth ring counting. Those obtained for three white coral colonies were 0.52 mm/y (n = 1), 0.60 mm/y (n = 1), and 0.36 ± 0.25 mm/y (n = 2). The radial growth rate for the bamboo coral colony was 0.13 mm/y in radius. The linear growth of the main steam of some colonies was analyzed from several cross sections. The linear growth rates of colonies could be estimated from the slope of the best fit curve (1) for increasing mean 210Pb concentration along the cross transects of the axis and (2) for increasing center 210Pb concentration of the skeleton axis. The linear growth rates calculated from the mean and center concentrations for two C. japonicum colonies were 8.5 and 6.1 mm/y, and 1.8 and 1.4 mm/y, respectively. Those for a P. elatius colony were 4.7 and 3.4 mm/y. The difference between the two estimates may reflect the morphological structure of the skeleton. The growth rates measured for the radial increase and linear extension of the main stem of the colonies could provide basic information for the demographic study of these coral species thereby fostering a rational exploitation of their populations.